Islam di Kota Ambon pada Masa Kolonial: Perspektif Sejarah - Steve Gerardo Christoffel Gaspersz (STT BNKP Sundermann, 2022)
The dynamic of development of Islam, either conceptually or institutionally, in Maluku should not be separated from the social history of Maluku society during colonial time of Westerners such as Portuguese and Dutch. This article attempts to reconstruct the dynamic of Islam especially in Ambon Island under colonization of the Dutch (VOC). The highly price of spices around sixteenth and seventeenth centuries had attracted many international traders coming to the spice island for trading spices (clove and nutmeg). Economic transaction and social interaction between local community of Ambon and foreign traders brought about significant social transformations mainly among indigenous people of Ambon, which was a trade center of spice at that time. Such social transformations escalated into political conflict between local community and Western colonizer (Dutch) who forced monopoly system of spice trading. Islam had been adhered by some local communities of Ambon at Leihitu Peninsula far before the Westerners was an important religion that conducted political-economic resistance and negotiated local identity facing colonial administration in Ambon at that time.